2009
DOI: 10.1063/1.3151712
|View full text |Cite
|
Sign up to set email alerts
|

Structural and optical properties of Mn-doped CdS thin films prepared by ion implantation

Abstract: We report on structural and optical properties of Mn-doped CdS thin films prepared by 190 keV Mn-ion implantation at different temperatures. Mn-ion implantation in the fluence range of 1×1013–1×1016 ions cm−2 does not lead to the formation of any secondary phase. However, it induces structural disorder, causing a decrease in the optical band gap. This is addressed on the basis of band tailing due to creation of localized energy states and Urbach energy calculations. Mn-doped samples exhibit a new band in their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(34 citation statements)
references
References 20 publications
1
33
0
Order By: Relevance
“…The reduced PL intensity of green emission indicates transfer of energy from excited carriers trapped at the surface to Mn 2+ ions. The orange emission ∼575 nm is due to 4 T 1 → 6 A 1 transition of Mn 2+ [15,20,[50][51][52][53][54]. Maximum orange emission intensity is found for 1 mol% Mn concentration.…”
Section: Photoluminescence Studymentioning
confidence: 85%
“…The reduced PL intensity of green emission indicates transfer of energy from excited carriers trapped at the surface to Mn 2+ ions. The orange emission ∼575 nm is due to 4 T 1 → 6 A 1 transition of Mn 2+ [15,20,[50][51][52][53][54]. Maximum orange emission intensity is found for 1 mol% Mn concentration.…”
Section: Photoluminescence Studymentioning
confidence: 85%
“…Further they reported that RE 3+ doped CdS nanocrystals show complete broadband absorption at well below their band edge to UV region. [9][10][11][12][13]. The methods stated above are very much sophisticated and highly complicated in procedure.…”
Section: Introductionmentioning
confidence: 98%
“…Also investigations of their optical properties are important to understand the electronic and band structure details. In general, Urbach energy are considered to be a telltale signature of the presence of different types of impurities, structural disorder, point defects and grain boundaries in amorphous chalcogenide glasses [2]. Also the heat treatment of chalcogenide films results in a decrease of the degree of disorder and defects present in these amorphous films [3], which is known to increase the optical energy gap.…”
Section: Introductionmentioning
confidence: 99%